REDUCING DEFECTS PRODUCT AT M.E. BAG AND PURSE PRODUCTION PROCESS USING DMAIC METHOD (The Indonesian Journal of Business Administration, 2021)
ME bag and purse is a start-up company engaged in fahion products. ME was established on 30 September 2017 in Yogyakarta. ME bag and purse provides women's bags in a variety of needs that are simple and chic in style, with good quality materials as well as neat stitches. We really pay attention to the details of our products as a good quality control. ME bag and purse are sold at affordable prices targeting the main market for teenagers and students.In this study, ME bag and purse uses several tools to analyze conditions and factors both inside and outside the company. ME bag and purse uses DMAIC methods and business process analysis to analyze the causes of waste and defects. Defining the process using the SIPOC diagram, then measurement to determine the criteria of product defect using CTQ (critical to quality), identify the kind of defect then to measure then determine the DPU, DPMO, and the sigma value to find out how big the defect is. Thus, to find out the causes of defective product in the production process using fishbone diagram. After analyzing through the fishbone diagram, the next step is to find a solution to the problem with the method in accordance with 6Ms (man, machine, material, method, milieu, measurement).Then as a manifestation of corrective measures, improvements and solutions were carried out with a new propose strategy based on recommendations for improvement, such as conduct training sewing and pattern making, performing maintenance on sewing machines, as well as utilizing the remaining defect material as value added items, applying the 5S concept for workstations, then using KPI (key performance index) as control tools to find out how far the recommendations for improvement are going and make the schedule timeline more organized.Keywords : ME bag and purse, defect product, DMAIC methods, business process analysis CTQ, DPU, DPMO, sigma value, 6Ms, KPI